A New Method to Estimate NPV and IRR from the Capital Amortization Schedule and the Advantages of the New Method - Kannapiran Arjunan (Australasian Accounting, Business and Finance Journal, 2022)
This paper introduces a new method, different from the discounted cash flow (DCF) method, for the first time, to estimate NPV and IRR. This method makes use of the capital amortization schedule (CAS). Accordingly, the present value (PV) of the closing balance (CB) in a CAS at a particular discount rate is the NPV at that rate and the interest rate that makes the CB zero is the IRR. CAS method also reveals that NPV represents the unutilised net cash flow (NCF) that remains as the CB in CAS. IRR is the only rate that fully utilize the NCF and makes the CB zero. The estimated NPV and IRR by CAS and DCF methods are perfectly matching in all cases of small or large-scale investments and under the financial and or economic analysis of investments. The CAS method is more transparent than the DCF method and provides a better insight into: a. evidence of reinvestment of intermediate income in some normal NCF and most non-normal NCF (NNCF) investments; b. elimination of the reinvestment income to get a unique IRR that resolves the problem of multiple IRR; and c. to identify the appropriate criterion between IRR and NPV, as NPV indicates the unutilised NCF whereas IRR indicates the return on invested capital (ROIC) by fully utilizing the NCF. The investors are comfortable to compare the IRR with the cost of capital in percentage term. As the modified IRR (MIRR) assumes reinvestment, MIRR might become redundant if there is no reinvestment and this is an incidental inference drawn.
Keywords: Cost-benefit Analysis; Net Present Value (NPV); Internal Rate of Return (IRR); Capital Amortization Schedule (CAS); Problems of Discounted Cash Flow (DCF).